Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films